2016
DOI: 10.1111/ejn.13216
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of DJ‐1/PARK7, the Parkinson's disease‐related protein, improves mitochondrial function via Akt phosphorylation on threonine 308 in dopaminergic neuron‐like cells

Abstract: DJ-1/PARK7, the Parkinson's disease-related protein, plays an important role in mitochondrial function. However, the mechanisms by which DJ-1 affects mitochondrial function are not fully understood. Akt is a promoter of neuron survival and is partly involved in the neurodegenerative process. This research aimed at investigating a possible relationship between DJ-1 and Akt signalling in regulating mitochondrial function in the dopaminergic neuron-like cells SH-SY5Y and PC-12. Overexpression of DJ-1 was firstly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 58 publications
0
23
0
Order By: Relevance
“…Drosophila carrying a mutant DJ-1β gene, the homologue of human DJ-1, show a reduced climbing ability reflecting locomotor defects ( Sanz et al, 2017 ). DJ-1 overexpression ameliorates mitochondrial function, including the mitochondrial quantity and activity of respiratory chain complex I, by phosphorylating Akt at Thr308 site in both SH-SY5Y and PC-12 cells ( Zhang et al, 2016 ). Recombinant DJ-1 can also reverse dopamine depletion in α-synuclein or 6-hydroxydopamine (6-OHDA)-triggered dopaminergic degeneration in vivo ( Batelli et al, 2015 ).…”
Section: Genetic Basis Of Pdmentioning
confidence: 99%
“…Drosophila carrying a mutant DJ-1β gene, the homologue of human DJ-1, show a reduced climbing ability reflecting locomotor defects ( Sanz et al, 2017 ). DJ-1 overexpression ameliorates mitochondrial function, including the mitochondrial quantity and activity of respiratory chain complex I, by phosphorylating Akt at Thr308 site in both SH-SY5Y and PC-12 cells ( Zhang et al, 2016 ). Recombinant DJ-1 can also reverse dopamine depletion in α-synuclein or 6-hydroxydopamine (6-OHDA)-triggered dopaminergic degeneration in vivo ( Batelli et al, 2015 ).…”
Section: Genetic Basis Of Pdmentioning
confidence: 99%
“…DJ-1 knockdown cells or DJ-1 knockout mice were prone to suffering cell death after treatment with H 2 O 2 or other neurotoxins (Yokota et al, 2003; Martinat et al, 2004; Chen et al, 2005; Kim et al, 2005b). The exact mechanisms of how DJ-1 protects against oxidative stress remain unclear, but it may enhance the phosphorylation of Akt (Kim et al, 2005a; Yang et al, 2005; Di Segni et al, 2006; Gorner et al, 2007; Van Der Brug et al, 2008; Aleyasin et al, 2010; Wang et al, 2014; Zhang et al, 2016). However, whether this capacity of DJ-1 functions in t-SCI is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, PC-12 cells have been widely served as a cellular model system for investigating PD ( Hatanaka, 1981 ; Westerink and Ewing, 2008 ), because they have the enzymes for dopamine synthesis, metabolism and transportation ( Hatanaka, 1981 ; Tuler et al, 1989 ). Our recent research demonstrated that DJ-1 could protect the mitochondria through enhancing the phosphorylation of Akt in MPP + -untreated PC-12 cells ( Zhang et al, 2016b ).…”
Section: Discussionmentioning
confidence: 99%
“…The simplified structure of plasmid for expression of DJ-1 as described previously ( Zhang et al, 2016b ), pcDNA3-Flag-DJ-1 (pDJ-1), is displayed in Figure 1 . The plasmid was validated by DNA sequencing and purified by the GoldHi plasmid kit (CoWin, Beijing, China) to remove endotoxin contamination.…”
Section: Methodsmentioning
confidence: 99%